Prophylaxis in congenital factor VII deficiency: Indications, efficacy and safety. Results from the Seven Treatment Evaluation Registry (STER) - Mariasanta Napolitano (2018)
Because of the very short half-life of factor VII, prophylaxis in factor VII deficiency is considered a difficult endeavor. The clinical efficacy and safety of prophylactic regimens, and indications for their use, were evaluated in factor VII-deficient patients in the Seven Treatment Evaluation Registry. Prophylaxis data (38 courses) were analyzed from 34 patients with severe factor VII deficiency ( < 1-45 years of age, 21 female). Severest phenotypes (central nervous system, gastrointestinal, joint bleeding episodes) were highly prevalent. Twenty-one patients received recombinant activated factor VII (24 courses), four received plasma-derived factor VII, and ten received freshfrozen plasma. Prophylactic schedules clustered into "frequent" courses (three times weekly, n=23) and "infrequent" courses (≤2 times weekly, n=15). Excluding courses for menorrhagia, "frequent" and "infrequent" courses produced 18/23 (78%) and 5/12 (41%) "excellent" outcomes, respectively; relative risk, 1.88; 95% confidence interval, 0.93-3.79; P=0.079. Long-term prophylaxis lasted from 1 to > 10 years. No thrombosis or new inhibitors occurred. In conclusion, a subset of patients with factor VII deficiency needed prophylaxis because of severe bleeding. Recombinant activated factor VII schedules based on "frequent" administrations (three times weekly) and a 90 μg/kg total weekly dose were effective. These data provide a rationale for long-term, safe prophylaxis in factor VII deficiency (clinicaltrials.gov: NCT01269138). © 2013 Ferrata Storti Foundation.